2017
DOI: 10.1186/s12888-017-1280-8
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms among survivors of Ebola virus disease in Conakry (Guinea): preliminary results of the PostEboGui cohort

Abstract: BackgroundThe 2013–2016 West African Ebola outbreak infected 28,616 people and caused 11,310 deaths by 11 May 2016, across six countries. The outbreak has also resulted in the largest number of EVD survivors in history—over 17,000. Guinea was declared Ebola-free on 1 June 2016. Reports from the outbreak documented 3814 cases resulting in 2544 deaths and 1270 survivors. EVD survivors face various neuropsychological and psycho-affective alterations that have not been fully identified yet. This study aims to docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
73
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 16 publications
4
73
0
3
Order By: Relevance
“…and receiving constant stares from the public after being discharged from the ETC. In similar studies conducted in Uganda, Sierra Leone and Guinea, EVD survivors reported feelings of frustration, anger, sadness and worthlessness due to a decline in quality of life and community neglect . Another Sierra Leonean study by Ji and colleagues reported that symptoms of obsession‐compulsion (83.3%), anxiety (83.3%), hostility (94.4%), phobic anxiety (94.4%) and paranoid ideation (72.2%) were more common among EVD survivors compared to medical staff, logistic staff, medical students and a Chinese medical team .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…and receiving constant stares from the public after being discharged from the ETC. In similar studies conducted in Uganda, Sierra Leone and Guinea, EVD survivors reported feelings of frustration, anger, sadness and worthlessness due to a decline in quality of life and community neglect . Another Sierra Leonean study by Ji and colleagues reported that symptoms of obsession‐compulsion (83.3%), anxiety (83.3%), hostility (94.4%), phobic anxiety (94.4%) and paranoid ideation (72.2%) were more common among EVD survivors compared to medical staff, logistic staff, medical students and a Chinese medical team .…”
Section: Resultsmentioning
confidence: 94%
“…The remaining three were cohort studies. Eighteen studies were from the 2013 to 2016 outbreak in West Africa the remaining six are from 1995 to 2012 outbreaks in Eastern Africa . Of the 24 papers, 23 were published in English and one published in French .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study showed that chronic post-SARS symptoms were characterized by sleep-related problems (Moldofsky and Patcai, 2011). Survivors of EVD also reported various sleep quality problems (Keita et al, 2017 In early December 2019, the first pneumonia case was identified in Wuhan, the capital city of Hubei province (Huang et al, 2020). With the spreading of the epidemic, Wuhan became the worst influenced area, where the mortality and incidence rate of COVID-19 were above the national level according to the National Health Commission of China (2020).…”
mentioning
confidence: 99%